Epiktet jako terapeuta współczesnego żołnierza: przypadek Jamesa Bonda Stockdale`a = Epictetus as a Therapist of a Modern Soldier: the case of James Bond Stockdale - Mróz, Tomasz (1975- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper aims to present the path which led J.B. Stockdale (1923-2005), a soldier and a pilot, to become interested in philosophy. Philosophy, with an emphasis on Stoicism and the texts of Epictetus, was transformed by him into a tool for surviving captivity during the Vietnam War. The article emphasises those components of Epictetus` thought that played a therapeutic role in Stockdale`s life, as they passed a practical test, and may become useful in the everyday life of a 21st-century humans.
Keywords: Stockdale, James Bond (1923-2005); Epiktet z Hierapolis (grecko-rzymski filozof; ok. 50-135); stoicyzm; wojna; transformacja; stoicism; war; transformation